Consolidation and Biodegradation Settlement Analysis of Embankment with Biosolid Layer Over Soft Subgrade - Rawat Saurabh; Kumar Gupta Ashok (E3S Web of Conferences)
The byproduct of wastewater treatment is called as ‘Biosolid’ whereas the byproduct of infrastructure sector produces construction and demolition (C&D) waste, both leading to major waste disposal problem. The present study evaluates the usage of biosolid as a potential fill material for embankments constructed over soft subgrade. Geotechnical and geochemical characterization of the virgin biosolid (VB) and 40% C&D waste modified biosolid (CNMB) has been conducted to evaluate their potential as fill materials. Consolidation and creep settlement behaviour of a 3m embankment under a traffic load of 20 kPa with VB and CNMB is investigated using Finite Element analysis (Plaxis 2D). Due to the organic nature of VB and CNMB, biodegradation settlement of the embankment is also analytically examined. The embankment with CNMB layer undergoes a settlement of 18.3 mm which is 62.3% lesser than embankment with VB layer over 365 days. The CNMB layer also attains constant rate of biodegradation after 20 years with 48.5 mm settlement which is within permissible limit. It is concluded that 40% C&D waste with biosolid can be used as fill material in embankment over soft subgrade. However, use of virgin biosolid as fill material is not recommended.